Melihat Lomba Estetika Keris Nasional, MengIngat Kriya Seni - M. Dwi Marianto (Ars: Jurnal Seni Rupa dan Desain, 2011)
This article is the result of a further research on the phenomenon of kris (Java traditional dagger),  a material presented in the discussion held in the Kris Aesthetics National Competition. It studied  this phenomenon appearing in daily life. Kris is very often misunderstood so that its potential to be the icon of Nusantara society remains uncovered. There are three points deliberated in this article, namely 1) Creative education, promotion, and socialization needed to endorse the kris industry  and its artistic value elevation; 2) An opportunity to set Kris in a new position not only as a mystical object but also as an aesthetic object; 3) The role of social institutions, higher education institutions on art-including ISI Yogyakarta (Indonesia Institute of the Arts Yogyakarta), and the public in developing the knowledge, the education and the practice of keris making with the spirit of innovation and contextuality. Those three things are important to be reviewed considering that UNESCO has announced kris as a world heritage.Keywords: kris, UNESCO, ISI Yogyakarta